1992
DOI: 10.1007/bf02352063
|View full text |Cite
|
Sign up to set email alerts
|

Subarachnoid hemorrhage of unknown origin. Longterm prognosis

Abstract: Patients suffering subarachnoid hemorrhage in whom angiography does not initially show vascular malformation and CT scan rules out an intracranial tumor, have, reportedly, a good prognosis with a rate of recurrent hemorrhage of about 2-10% within a follow-up time of up to 15 years. Most authors denied indication for control angiography. In order to study the benefit of control angiography performed after 4-6 weeks, four-hundred eighty-three patients with SAH but without ICH were reveiwed, and the longterm clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…1,3,4,14 However, according to different studies, a bleeding source is not identified on the first DS angiogram in up to 27% of cases. 8,11,12,13,16 The reason could be initial local vasospasm or occlusion of the ruptured aneurysm due to blood clots. 12 Authors of a number of studies have proved an initial nonfilling aneurysm on a second DS angiogram.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,4,14 However, according to different studies, a bleeding source is not identified on the first DS angiogram in up to 27% of cases. 8,11,12,13,16 The reason could be initial local vasospasm or occlusion of the ruptured aneurysm due to blood clots. 12 Authors of a number of studies have proved an initial nonfilling aneurysm on a second DS angiogram.…”
Section: Discussionmentioning
confidence: 99%
“…12 Authors of a number of studies have proved an initial nonfilling aneurysm on a second DS angiogram. 4,12,13,17 Jung et al 11 postulate that about 60% of all cases of SAH with negative DS angiograms can be attributed to PM SAH. Given our results of 26.3% patients with PM SAH, the incidence of 60% seems very high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the risks of morbidity and mortality associated with aneurysmal SAH are high, prognosis is better for SAH due to causes other than aneurysm rupture. [5][6][7][8][9] Perimesencephalic SAH as described by Van Gijn et al is representative of non-aneurysmal SAH, is known to have almost no risk of rebleeding, and is associated with good recovery. 10 Accordingly, when the cause of the haemorrhage cannot be found on the first cerebral angiogram it is important to distinguish between causal factors that are the most clinically serious; that is, whether a cerebral aneurysm exists but cannot be found, or whether the haemorrhage is a result of other unknown causes.…”
Section: Introductionmentioning
confidence: 97%